Pengaruh Labelisasi Halal, Personal Selling dan Online Customer Review Terhadap Keputusan Pembelian (Studi Pada Follower Instagram Scarlett Whitening) - Fitrah Rahma Inayah; Idris Parakkasi; A Syathir Sofyan (Al Maal: Journal of Islamic Economics and Banking, 2023)
This study aims to determine the effect of halal labeling, personal selling and online customer reviews on purchasing decisions for Instagram followers of Scarlett Whitening products. This study uses a quantitative analysis approach using multiple linear regression analysis techniques. Primary data was obtained through a questionnaire distributed to respondents, namely Scarlett Whitening's Instagram followers. The sample of this study amounted to 348 people. The results of this study indicate that there is no influence of halal labeling on purchasing decisions, while personal selling and online customer reviews have an influence on purchasing decisions for Scarlett Whitening products.